The Role of Case Titles and Reconstruction in Strengthening Investigators' Confidence in Crime Evidence - Sadida, Qaulan (Annual Review of Legal Studies, 2024)
The law enforcement process for suspected criminal acts begins with an investigation process by the police. The investigation is carried out with the intention of finding and discovering an event suspected of being a criminal act so that the next stage can be carried out, namely the investigation. This study uses a normative legal research type with a qualitative approach. Based on secondary data and primary data. The results of this study indicate that: (1) The role of case titles and reconstruction in the Indonesian criminal justice system is as a guide in the process of investigating criminal acts. (2) Case titles and reconstruction play a role in helping investigators collect evidence and strengthening investigators' confidence in collecting evidence to uncover a crime. The conclusion of this study is that case titles play a role in helping investigators collect evidence, while reconstruction plays a role as indicative evidence that strengthens investigators' confidence in uncovering criminal acts.